THE EFFECT OF POWER LIMBS, SPEED REACTION, FLEXIBILITY AND SELF CONFIDENCE ON THE ACHIEVEMENT OF ELITE ATHLETES ATHLETIC WEST JAVA IN THE TRACK NUMBER - Anggi Setia Lengkana; James Tangkudung; Moch. Asmawi (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2018)
This study aims to reveal the effect of limb power, reaction speed, flexibility and confidence in the performance of athletic elite athletes on track numbers. This research was conducted at Universitas Pendidikan Indonesia (UPI) Lab. Sport Faculty of Sport and Health Education (FPOK), with a sample of 31 athletes. The analytical technique used in this study is to use path analysis (Path Analysis), with the aim to identify the influence between variables. The results showed that: (1). Power Limbs affect the achievement of elite athletes by 51.7%. (2). The speed of the reaction had an effect on the achievement of elite athletes by 49.3%. (3). Flexibility has no effect on elite athletes achievement of 0.3%. (4). Confidence affects the achievement of elite athletes by 20%. (5). Limb power affects 40.5% confidence. (6). The speed of the reaction affects the confidence of 30.7%. (7). Flexibility has no effect on confidence of 23.2%. Keywords: Performance of elite athlete, athletic, limb power, reaction speed, flexibility and self confidence